Prevalence of depression and its association with quality of life in patients after pacemaker implantation during the COVID-19 pandemic: A network analysis - Lin, Yun; Cai, Hong; Liu, Hong-Hong; Su, Xue-Jian; Zhou, Chen-Yu; Li, Jing; Tang, Yi-Lang; Jackson, Todd; Xiang, Yu-Tao (Frontiers in Psychiatry, 2023)
Background: The study aimed to investigate the prevalence of depression and factors associated with quality of life (QOL) in patients after pacemaker implantation using network analysis (NA) during the COVID-19 pandemic. Methods: This cross-sectional, observational study was conducted in China between July 1, 2021, and May 17, 2022. Univariate analyses were used to compare differences in demographic and clinical characteristics between depressed and non-depressed patients following pacemaker implantation. Binary logistic regression analysis was used to assess factors independently associated with depression. Network analysis index of “Expected influence”, and flow function were used to identify symptoms central to the depression network of the sample and depressive symptoms that were directly associated with QOL, respectively. Network stability was examined using a case-dropping bootstrap procedure. Results: In total, 206 patients implanted with a pacemaker met the study entry criteria and completed the assessment. The overall prevalence of depression (PHQ-9 total score ≥ 5) was 39.92% (95% confidence interval (CI)=29.37-42.47%). A binary logistic regression analysis revealed that patients with depression were less likely to have a perceived good health status (p=0.031), and more likely to report more severe anxiety symptoms (p<0.001) and fatigue (p<0.001). In the network of depression, “Sad mood”, “Poor Energy” and “Guilt” were the most influential symptoms. Furthermore, “Fatigue” had the strongest negative association with QOL, followed by “Sad mood” and “Appetite”. Conclusion: Depression was common in patients after pacemaker implantation during the COVID-19 pandemic. Anxiety, central symptoms of depression (e.g., “Sad mood”, “Poor Energy” and “Guilt”) and depressive symptoms linked to QOL (e.g., “Sad mood”, “Appetite” and “Fatigue”) identified in this study could be targeted for interventions and preventive measures for depression in patients who have undergone pacemaker implants.